Distribution and Pathogenic Potential of Soil Fusaria from Selected Oil Palm Habitats in West Malaysia - Ho, Yin Wan (1984)
A total of eight species and two varieties of Fusarium was isolated from the sampling sites in the oil palm habitat. Fusarium solani and Fusarium oxysporum were the most prevalent species followed by Fusarium semitectum. The other species and varieties isolated showed a more sporadic occurrence. Generally, soils from oil palm rhizospheres and young palm areas contained a larger number and greater variety of Fusarium species than soils from the avenues and older palm areas. Pathogenicity tests of Fusarium species isolated showed that none were capable of producing vascular wilt or other diseases on oil palm seedlings. Some of the isolates, however, caused a reduction of growth in the test seedlings. Comparative studies of F. oxysporum isolates from oil palm habitat in Malaysia with F. oxysporum f. sp. elaeidis isolates from Africa showed that the two groups of isolates were ind istinguishable in their cultural, morphological and isozyme characteristics. Subsequent pathogenicity tests proved that the F. oxysporum isolates from Africa were pathogenic, causing vascular wilt on the Malaysian oil palm seed lings whilst the F. oxysporum isolates from Malaysia were non-pathogenic to the wilt-susceptible African oil palm seed lings and Malaysian oil palm seed lings. Inoculation of Malaysian F. oxysporurn isolates on Malaysian oil palm seedlings and wilt-susceptible African oil palm seedlings, subjected to an initial period of water stress, also did not result in showing any d isease symptoms.